Analisis Ketidakjujuran Akademik Pada Mahasiswa Calon Guru Kejuruan Bidang Teknik Mesin - Hendra Setyawan; Muhammad Akhyar; Indah Widiastuti (Nozel : Jurnal Pendididikan Teknik Mesin, 2021)
Academic dishonesty is considered as one of the disgraceful behaviors that damage the character of students. Considering the important role of teachers in preventing fraud in the learning process, teacher candidate education programs are expected to have a conducive environment to uphold academic integrity. mechanical engineering vocational. This research is a quantitative descriptive study conducted in one of the educational staff educators at a public university in Central Java. Data collection techniques using a survey instrument with a total of 117 students as respondents. The validity and reliability of the data using the help of a statistical data processing software. The results showed that the indications of academic dishonesty of vocational engineering students were 92.3% had been involved in collaborating when doing assignments, 91.5% had been involved in collaborating during exams, 85.5% had been involved in copying and pasting assignments, as much as 98.3%. Never been involved in not reporting cheating in class, opening cell phones for browsing during exams, and fake attendance. The causes of academic dishonesty of vocational engineering students are not ready to face exams, exam questions and heavy assignments, lack of firmness of supervisors, the majority of students do it, the absence of strict rules and punishments. The solution to overcome the academic dishonesty of vocational engineering students is a warning when violating, confirming the supervisor, making the majority of students stop cheating, confirming rules and punishments, making the classroom situation impossible for cheating, ensuring student readiness for exams, prohibiting carrying cell phones when exam and spaced out seats during the exam. The results of this study are expected to be used for efforts to handle and prevent academic dishonesty in teacher education in general.